Implementación de un sistema eléctrico residencial de cinco pisos tipo trifásico de 220 v de 30 kVA Edificio Gaitán Diagonal 79b Bis #56-61, Bogotá (2022)
Three-phase distribution systems are the way more efficient than the companies supplying the electrical energy used to distribute to the consumers, based on the parameters established by the technical regulation electrical installations (RETIE) and NTC 2050, the which is essential for all electrical work. According to the ministry of mines and energy, the project It is oriented to buildings with a maximum of five stories high, providing users feasible, effective and economical solutions for resolve or regulate these parameters within the established ranges of the RETIE technical regulation as the main base, for this the materials to used will be new, of brands that accredit their quality in the national market, preferably qualified in material relations highly certified electricians, the implementation of the electrical system of the building included from medium voltage connections and their respective distribution branches, the building Gaitán, made up of 5 floors, is located in Diagonal 79 b bis No 56 – 61 Bogotá.